Analisis Perbandingan Pendapatan dan Efisiensi Usaha Briket Tongkol Jagung, Briket Batok Kelapa, dan Arang di Desa Cupak, Ngusikan, Kabupaten Jombang - Maghfiroh, Canggih Nailil; Puspaningrum, Yessita; Hartati, Dyah Ayu Sari (Program Studi Agribisnis, 2024)
Indonesia, as an agrarian country, has significant potential in utilizing agricultural waste for alternative energy. This study aims to analyze the income and production efficiency of briquettes made from corn cobs, coconut shells, and wood charcoal in Cupak Village, Ngusikan, Jombang Regency, focusing on the Break-Even Point (BEP), total production cost, monthly income, and production efficiency. Corn cob briquettes have the lowest BEP (343 units and Rp 3,432,343), the lowest total production cost (Rp 11,310,000), and the highest monthly income (Rp 6,557,500), making them the most economical and profitable with the best production efficiency (6.9). Coconut shell briquettes have a higher BEP (366 units and Rp 3,667,711), higher production costs (Rp 17,460,000), and a monthly income of Rp 6,045,000, but offer high quality and market value, suitable for the premium market despite lower efficiency (4.1). Wood charcoal has the highest BEP (580 units and Rp 4,064,516), the highest production cost (Rp 17,760,000), and the lowest monthly income (Rp 4,875,000), making it the least efficient (3.2) but still attractive for the premium market.